Digital transfrmation model of education processes through cloud services - Stefanović Nenad D.; Plašić Jelena M. (University of Kragujevac - Faculty of Pedagogy, Užice, 2020)
Education in the 21st century is confronted with many challenges - it needs to be personalized, adaptive to user needs, collaborative, social, multimedial, and technologically supported. The development of information technologies such as cloud computing, mobile technologies, platforms for social networking and collaboration, and intelligent systems, has created enormous opportunities for improvement of the education processes. In order to ensure required quality level, educational institutions are forced to enter the digital transformation process. In this paper, the analysis of the existing state of the education system and overview of the existing results in the digital transformation are given. Process model for digital transformation of education that encompasses the entire lifecycle, as well as the framework for implementation of cloud digital services with basic phases and steps is presented. The concrete use cases of application of the digital services in teaching and learning are shown. The results obtained show efficiency and effectiveness of the proposed process model and the framework, as well as the cloud-based digital platform. The main benefits include a higher satisfaction level of students and teachers, better exam results, more intensive collaboration and communication, knowledge exchange, lower costs, as well as a better reliability and security of the system. Service for monitoring and data analysis enable more efficient decision making and taking actions for improvements.